1999
DOI: 10.1007/s002940050464
|View full text |Cite
|
Sign up to set email alerts
|

Molecular karyotypes for Alternaria plant pathogens known to produce host-specific toxins

Abstract: There are at least ten plant diseases caused by Alternaria species in which host-specific toxins (HSTs) are responsible for fungal pathogenicity. Of these HST-producers, seven are considered distinct pathotypes of the species Alternaria alternata, and the remaining three are among other species of pathogenic Alternaria. Inter- and intra-specific variation among Alternaria taxa, including HST-producers, was determined by electrophoretic karyotyping using pulsed-field gel electrophoresis. A. alternata including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 57 publications
2
70
0
7
Order By: Relevance
“…The weak signal obtained for ECs in almost all isolates was probably due to hybridization of the probe to rDNA, given that rDNA is a highly multicopy gene and it is difficult to remove the trace amounts of contaminating rDNA from the probe DNA. The chromosomes demonstrating weak signal corresponded to those harboring rDNA sequences (5). The nature of the 1.0-Mb chromosome is in agreement with the criteria determined for supernumerary chromosomes (10).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The weak signal obtained for ECs in almost all isolates was probably due to hybridization of the probe to rDNA, given that rDNA is a highly multicopy gene and it is difficult to remove the trace amounts of contaminating rDNA from the probe DNA. The chromosomes demonstrating weak signal corresponded to those harboring rDNA sequences (5). The nature of the 1.0-Mb chromosome is in agreement with the criteria determined for supernumerary chromosomes (10).…”
Section: Resultssupporting
confidence: 87%
“…There is also clear evidence of recent lateral gene transfer of the ToxA gene from Stagonospora nodorum to P. tritici-repentis (14,30). In Alternaria alternata plant pathogens (37), we have shown that all strains of the A. alternata pathotypes harbor small extra chromosomes of less than 1.7 Mb, whereas nonpathogenic isolates do not have these small chromosomes (5). A cyclic peptide synthetase gene, AMT, which is involved in host-specific AM toxin biosynthesis of the apple pathotype of A. alternata, was located on a small chromosome of 1.1 to 1.7 Mb, depending on the strain (22,23).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…異的 AAL 毒素を生産し,愛知ファーストなどの特定のトマ ト品種に病気を引き起こす (Akamatsu et al, 1997;Gilchrist & Grogan, 1976;Peever et al, 2004) .本毒素は,Fusarium 属 病原菌が生産するマイコトキシンのフモニシンに化学構造 および生物活性が類似している (Bottini et al, 1981;Caldas et al, 1995;Musser and Plattner, 1997) (Bojja et al, 2004;Butchko et al, 2006;Proctor et al, 2003Proctor et al, , 2006 (Akagi et al, 2009a, b;Akamatsu et al, 1999;Covert, 1998;Johnson et al, 2001 …”
Section: Arborescens,茎枯病菌)は,ポリケチド化合物である宿主特unclassified
“…This method was further modifi ed and developed for various other fungal species during the past decade (3)(4)(5)(6)(7)(8)(9) . Basically, conidia are suspended in complete medium and placed on a glass slide for germination.…”
mentioning
confidence: 99%